Occupational Health and Safety Knowledge correlated with The Use of PPE among Home Industry Furniture Workers in the Production Process - Nur Aini Fatimah; Hepfi Sofiana; Henny Purwandari; Risa Nurhayati (Journal of Ners and Midwifery, 2023)
Work accident is an unexpected event that can cause loss and damage to both physical, and property and cause death. One way to prevent work accidents is to increase understanding related to occupational health and safety so that workers have the behavior of using Personal Protective Equipment (PPE) in accordance with the need to protect themselves in order to avoid work accidents. The aim of this study was to determine the correlation between knowledge about occupational health and safety and the use of Personal Protective Equipment (PPE) for furniture home industry workers in the production process in Balongrejo Village, Berbek District, Nganjuk Regency. The design of the study used correlational with a cross-sectional approach with a total of 42 respondents which selected by the Proportional Random Sampling technique. The independent variable in this study was knowledge of occupational health and safety and the dependent variable was the use of personal protective equipment (PPE). The results of the Spearman rank test showed that there was a correlation between Occupational Health and Safety Knowledge and the use of PPE for Home Furniture Industry workers in the production process in Balongrejo Village, Berbek District, Nganjuk Regency with strong correlation strength. The knowledge of workers with the behavior of using PPE is directly proportional so that the better the knowledge possessed, the better the behavior reflected, therefore it is important for nurses as educators to provide education to workers regarding the use of personal protective equipment